Pengaruh Rotasi Audit, Reputasi Auditor dan Biaya Audit terhadap Kualitas Audit: Studi dengan Pendekatan Earning Surprise Benchmark - Khomsiyah; Esteti Handayani Hia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The primary aim of this research is to investigate the impact of audit rotation, auditor reputation, and audit fees on audit quality, utilizing the Earnings Surprise Benchmark as a proxy. The study employs a purposive sampling method, focusing on manufacturing companies in the ASEAN-5 (Indonesia, Malaysia, Philippines, Singapore, and Thailand) listed on S&P Capital IQ from the period of 2019-2022. A quantitative approach is adopted, with data analysis conducted using STATA version 17 and a logistic regression method. The findings indicate that audit rotation and audit fees impact audit quality positively but insignificant impact on audit quality. While auditor reputation has a negative but insignificant impact on audit quality.